Thick film conductor, composition for forming the same, and thick film conductor paste containing the composition for forming the same
The use of a thick film conductor paste with specific conductive and lead-free glass powders addresses the issue of glass component emergence, ensuring stable electrical connections and adhesion in conductor layers on glass glaze substrates.
Patent Information
- Application Number
- JP2020201873
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-04
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-12-04
AI Technical Summary
The formation of thick film conductor layers on glass glaze substrates results in the emergence of glass components on the surface, leading to poor or unstable electrical connections.
A thick film conductor paste composition containing conductive powders such as Au, Ag, or Pd, and a lead-free glass powder system with V2O5-ZnO-Bi2O3, which suppresses the emergence of glass components on the surface during firing.
The composition effectively prevents glass components from appearing on the surface of the conductor layer, ensuring stable electrical connections and improved adhesion to the substrate.
Smart Images

Figure 0007622412000004 
Figure 0007622412000005 
Figure 0007622412000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a thick-film conductor formed on a substrate having a glass-containing film formed on its surface, such as a glass glaze substrate, a composition for forming the same, and a thick-film conductor paste containing the composition for forming the same. [Background technology]
[0002] Thermal printers, a type of printing device that uses heat to print on paper media such as thermal paper and thermal transfer ribbons made of thermally reactive materials, are characterized by low cost, low noise, and maintenance-free operation, and are used in a wide range of applications such as home facsimiles and ticket vending machines. Among these thermal printers, the thermal printhead, which is the device that prints on the above-mentioned paper media, is mainly composed of a glass glaze substrate, electrodes with a predetermined pattern formed on the surface of the substrate, a resistor that generates heat when electricity is applied through the electrodes, and a driver IC that drives these components.
[0003] For example, Patent Document 1 discloses a thermal printhead comprising a glass glaze substrate having a glass glaze layer formed by printing and firing a glass paste or the like on the surface of a ceramic substrate such as alumina, electrodes and heating resistors formed on the surface of the glass glaze substrate by thick-film technology using a conductive paste and a resistive paste, respectively, as raw materials, and a protective layer that is abrasion-resistant and smooth and is formed by applying glass paste to cover the electrodes and heating resistors and firing the glass paste.
[0004] The conductor paste is generally prepared by dispersing a metal powder such as silver powder and a glass powder as a binder in a paste-like vehicle. Meanwhile, the resistor paste is generally prepared by dispersing a conductive powder such as ruthenium oxide and a glass powder as a binder in a paste-like vehicle. The vehicle used for the conductive paste and resistor paste is generally prepared by dissolving a resin or the like in an organic solvent. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2002-127483 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, since the substrate of the thermal printhead is a ceramic substrate covered with a glassy glass glaze layer, problems can arise when the thick-film conductor paste used as a material for forming a conductor layer such as an electrode directly on the surface of the ceramic substrate is used as is. That is, when the thick-film conductor paste containing the thick-film conductor composition used as a material for forming a conductor layer directly on the surface of the ceramic substrate is printed on the surface of the glass glaze layer and fired, the glass component is raised (sometimes called seepage) on the surface of the conductor layer thus formed, and when the surface of the conductor layer is used as a terminal for electrical connection or when an element such as a resistor is formed in a state electrically connected to the surface of the conductor layer, the electrical connection can become poor or unstable.
[0007] The present invention has been made in consideration of the above circumstances, and provides a glass glaze substrate. of Thus, the object of the present invention is to provide a composition for forming a thick film conductor, which prevents glass components from floating out onto the surface of a thick film conductor layer formed by firing on a substrate having a glass-containing film formed on its surface, and a thick film conductor paste containing the composition. [Means for solving the problem]
[0008] In order to achieve the above object, the present invention provides a composition for forming a thick-film conductor, which comprises a conductive powder and a lead-free glass powder containing vanadium and zinc, and is used as a raw material for a thick-film conductor layer formed by firing on a substrate having a glass-containing film formed on the surface thereof. The conductive powder is a metal powder or an alloy powder selected from the group consisting of Au, Ag, Pd, and Pt, and the lead-free glass powder is V. 2 O 5 -ZnO-Bi 2 O 3 The vanadium-based glass powder is made of vanadium oxide V 2 O 5 The zinc content is 30 to 60 mass % in terms of zinc oxide, and the zinc content is 20 to 50 mass % in terms of zinc oxide, ZnO. It is characterized by: Effect of the Invention
[0009] According to the present invention, even when a thick-film conductor layer is formed by firing on a substrate having a film containing glass formed on its surface, it is possible to prevent the glass component from coming to the surface. [Brief description of the drawings]
[0010] [Figure 1] 1 is a SEM photograph (×5000) of a thick-film conductor of a comparative example of the present invention. [Diagram 2] 1 is a SEM photograph (×5000) of a thick-film conductor according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] 1. Thick-film conductor forming composition The composition for forming a thick-film conductor according to the embodiment of the present invention is a composition for forming a thick-film conductor when a glass glaze layer is formed on a substrate surface. Taga It is used as a raw material for a thick-film conductor layer formed by firing on a substrate having a glass-containing film formed on its surface, such as a lath glaze substrate, and contains a conductive powder and a lead-free glass powder containing vanadium and zinc. Below, the conductive powder and the lead-free glass powder will each be explained, and then the composition for forming a thick-film conductor will be explained in detail.
[0012] 1.1 Conductive powder The conductive powder, which is one of the main components of the thick-film conductor forming composition of the embodiment of the present invention described above, may be a material used for general thick-film conductors, and for example, noble metals such as Au, Ag, Pd, and Pt are preferably used, and are used in the form of a single metal powder consisting of only one type selected from the group consisting of these noble metals, or an alloy powder thereof, or a mixed powder combining two or more of these single metal powders or alloy powders. Among these, it is preferable to use a powder of Ag alone or a mixed powder of Ag with Pd alone, an alloy powder of Ag and Pd, or a mixed powder thereof, in terms of low melting point and cost.
[0013] The number average particle size of the conductive powder is preferably 10 μm or less, and more preferably 0.1 μm or more and 5.0 μm or less from the viewpoint of coating property when prepared in the form of a thick-film conductor paste. If the number average particle size exceeds 10 μm, the temperature rise time may be too long during firing. In addition, when using two or more types of mixed powders such as a mixed powder of Ag powder and Pd powder, it is preferable to use powders with different number average particle sizes from the viewpoint of coating property when prepared in the form of a thick-film conductor paste and from the viewpoint of uniform dispersion of these different types of powders. For example, it is preferable to mix a metal powder with a small particle size of about 1 / 10 to 1 / 2 with the above-mentioned metal powder with a number average particle size of 0.1 μm to 5.0 μm. Specifically, in the case of a mixed powder of Ag powder and Pd powder, it is preferable to set the number average particle size of Ag powder to 0.1 μm to 3.0 μm and the number average particle size of Pd powder to 0.01 μm to 0.3 μm.
[0014] When two or more kinds of mixed powders are used as described above, it is preferable to mix the metal powder having the largest number average particle size in an amount of 10 to 80 parts by mass when the total mixed powder is taken as 100 parts by mass. Here, the number average particle size is the arithmetic average of the lengths of the particle groups in the SEM image obtained by imaging the powder to be measured with a scanning electron microscope. The shape of the conductive powder is not particularly limited, and various shapes such as granular, clumpy, and flake-like shapes can be used. A suitable shape may be appropriately selected depending on the application. A thick-film conductive paste is prepared using this conductive powder as described later, and the paste is applied and fired to form a thick-film conductor layer having a predetermined pattern shape.
[0015] 1.2 Lead-free glass powder containing V and Zn The lead-free glass powder, which is the other main component of the thick-film conductor forming composition according to the embodiment of the present invention, contains V and Zn. This lead-free glass powder may further contain alkaline earth elements such as Ba and Ca, or may contain B, Bi, and Al. Examples of such lead-free glass include glass powders such as V2O5-ZnO-alkaline earth oxide glass powder, V2O5-ZnO-B2O3 glass powder, and V2O5-ZnO-Bi2O3 glass powder. In addition to the above-mentioned additive elements, Si, Fe, Cu, and the like may be added to the lead-free glass powder.
[0016] The lead-free glass powder containing V and Zn contains 30 to 60 mass % of V calculated as its oxide, V2O5, and n It is preferable to mix V in an amount of 20 to 50 mass % calculated as its oxide ZnO. The addition of V changes the thermal melting property of the lead-free glass, so that if V is less than 30 mass % calculated as the oxide V2O3, the glass transition point will be higher than the upper limit of the desirable temperature range described below, and conversely, if it exceeds 60 mass %, the glass transition point will be lower than the lower limit of this desirable temperature range.
[0017] On the other hand, if the amount of Zn exceeds 50 mass% in terms of oxide ZnO, it becomes difficult to vitrify, and conversely, if it is less than 20 mass%, the effect of adding Zn becomes difficult to obtain. This lead-free glass containing V and Zn may be crystallized glass or may be glass that does not crystallize. In the present invention, the lead-free glass powder is defined as a glass powder that does not contain lead or a glass powder that contains 100 mass ppm or less of lead as an unavoidable impurity.
[0018] Considering the firing temperature when forming a thick-film conductor by firing the thick-film conductive paste, it is desirable that the glass transition point of this lead-free glass powder containing V and Zn is 350°C or more and 550°C or less. If the glass transition point is less than 350°C, glass protrusion described below may occur on the surface of the thick-film conductor. Conversely, if the glass transition point exceeds 550°C, staining described below may occur. Here, the glass transition point can be determined as the temperature at the point showing the bending point of the thermal expansion curve obtained by measuring in air by thermomechanical analysis (TMA) for a rod-shaped sample formed by remelting the glass powder to be measured.
[0019] The shape of the lead-free glass powder containing V and Zn is not particularly limited, and various shapes such as spherical and needle-like can be used. In addition, the lead-free glass powder containing V and Zn preferably has a D50 diameter (median diameter) of a volume cumulative particle size distribution measured by a particle size distribution meter using laser diffraction of 0.5 μm to 30 μm. If the lead-free glass powder has a particle size distribution within this range, when the lead-free glass powder is mixed with the conductive powder described above to produce the thick-film conductor forming composition of the embodiment of the present invention, the lead-free glass powder is efficiently ground, so that the conductive powder and the lead-free glass powder become finer and can be uniformly dispersed.
[0020] 1.3 Composition for forming thick-film conductor By including the above-mentioned conductor powder and glass powder in a composition for forming a thick film conductor, when the composition is prepared into a conductor paste form and applied to the surface of a ceramic substrate such as alumina and fired to form a thick film conductor, the glass powder acts to further strengthen the adhesion between the ceramic substrate and the thick film conductor.
[0021] Incidentally, if the inclusion of glass in the thick film conductor composition as described above increases the adhesive strength of the thick film conductor formed on the surface of a ceramic substrate using this composition as a material, then when a glass-containing film such as a glass glaze layer is formed on the surface of the ceramic substrate, it would appear that the thick film conductor forming composition, which is the material for the thick film conductor formed on that surface, does not need to contain glass powder in order to strengthen adhesion to the ceramic substrate.
[0022] However, when a composition for forming a thick-film conductor contains only a conductive powder such as Ag powder without containing glass powder, the thick-film conductor formed on the surface of a glass glaze layer using the composition for forming a thick-film conductor as a material may have a problem in that the glass component floats to the surface, reducing the electrical conductivity. Since the composition for forming a thick-film conductor does not contain glass powder, the floated glass component originates from the glass glaze layer.
[0023] In this case, it is difficult to predict that the glass component will come out on the surface of the thick-film conductor formed on the surface of the glass glaze layer. This is because, when forming a thick-film conductor, if a glass paste containing glass powder, which is the material of the glass glaze layer, is applied to the surface of the ceramic substrate and is not yet fired, a thick-film conductive paste containing a composition for forming a thick-film conductor is applied to the surface of the glass paste layer, and the unfired glass paste layer and the thick-film conductive paste layer are fired simultaneously, the glass powder of the unfired glass paste layer melts, and the glass component diffuses from the glass paste layer, which has an excessive concentration of glass component, toward the composition for forming a thick-film conductor, which has a zero concentration of glass component, and this makes it easier for the glass component to come out on the surface of the thick-film conductor after firing. On the other hand, when a thick-film conductor is formed by applying and firing a thick-film conductive paste to the surface of a glass glaze layer, which is a film containing glass that has already been fired into a film, it is difficult to predict that the glass component will diffuse to the surface and come out.
[0024] In contrast, the composition for forming a thick film conductor according to an embodiment of the present invention contains lead-free glass containing V and Zn, as described above. Therefore, even when a thick film conductor layer is formed by applying and firing a thick film conductive paste containing the composition for forming a thick film conductor to the surface of a glass-containing film formed by applying and sintering a glass paste containing glass powder to the surface of a ceramic substrate, such as a glass glaze substrate, the glass components can be prevented from floating up to the surface of the thick film conductor layer.
[0025] The thick-film conductor forming composition according to the embodiment of the present invention is preferably formulated so that the lead-free glass containing V and Zn is 0.8 parts by mass or more and 4 parts by mass or less per 100 parts by mass of the conductive powder. If the blending ratio of the lead-free glass containing V and Zn is less than 0.8 parts by mass, it may not be possible to suppress the protrusion of the glass component on the surface of the thick-film conductor after firing. Conversely, even if the blending ratio of the lead-free glass containing V and Zn exceeds 4 parts by mass, the effect of suppressing the protrusion of the glass component is almost the same, which is uneconomical.
[0026] Even when a composition for forming a thick-film conductor containing V2O5 powder is used instead of lead-free glass containing V and Zn, the glass components can be prevented from emerging onto the surface of the thick-film conductor formed by firing. In this case, however, a blotchy pattern known as a stain, which can be observed with a scanning electron microscope (SEM), may appear on the surface of the glass glaze layer surrounding the thick-film conductor.
[0027] This stain may adversely affect the thick-film conductor, and may cause poor or unstable electrical connection when the thick-film conductor is used as a terminal for electrical connection or when an element such as a resistor is formed in a state where the thick-film conductor is electrically connected to the thick-film conductor. In contrast, the composition for forming a thick-film conductor according to the embodiment of the present invention can effectively prevent both the protrusion of glass components and the occurrence of stains on the surface of the thick-film conductor obtained after firing, making the above-mentioned electrical connection problems less likely to occur.
[0028] The thick-film conductor forming composition according to the embodiment of the present invention may contain glass powder not containing V in addition to the lead-free glass containing V and Zn. This can impart properties such as improved chemical resistance to the thick-film conductor when Ni electroplating is performed on the surface of the thick-film conductor. Even when the glass powder not containing V is contained, it is preferable to contain 0.8 parts by mass or more of the lead-free glass containing V and Zn with respect to 100 parts by mass of the conductive powder, which can suppress the protrusion of the glass component on the surface of the thick-film conductor. The amount of the glass powder not containing V to be added is not particularly limited and can be appropriately selected depending on the purpose of use of the thick-film conductor, but it is generally desirable to contain 0.8 to 3 parts by mass with respect to 100 parts by mass of the conductive powder.
[0029] The V-free glass powder may be a lead-free glass powder such as SiO2-B2O3-alkaline earth oxide glass powder, Bi2O3-SiO2-B2O3 glass powder, or ZnO-SiO2-B2O3 glass powder, or a SiO2-B2O3-PbO glass powder. Among these, it is preferable to use a lead-free glass powder in consideration of recent environmental protection. In addition, in consideration of the firing temperature when forming a thick-film conductor by firing, the above-mentioned V-free lead-free glass powder preferably has a glass transition point of 400°C or more and 600°C or less, or a softening point of 500°C or more and 700°C or less, or satisfies both the temperature conditions of the glass transition point and the softening point.
[0030] Furthermore, it is desirable that the glass transition point of the above-mentioned lead-free glass not containing V is equal to or lower than the glass transition point of the glass constituting the glass-containing film formed on the surface of the ceramic substrate, or the softening point of the above-mentioned lead-free glass not containing V is equal to or lower than the softening point of the glass constituting the glass-containing film formed on the surface of the ceramic substrate. As with the glass transition point of the above-mentioned lead-free glass powder containing V and Zn, the glass transition point of the lead-free glass powder not containing V can be determined as the temperature of a point showing an inflection point of a thermal expansion curve obtained by measuring in air by thermomechanical analysis (TMA) a rod-shaped sample formed by remelting the glass powder to be measured.
[0031] The glass transition point and softening point conditions of the V-free glass powder can be satisfied by appropriately adjusting the glass composition. In addition, the V-free glass powder preferably has an SiO2 content of 15% by mass or more and 60% by mass or less. If the SiO2 content is less than 15% by mass, the weather resistance, water resistance, and chemical resistance of the glass in the thick-film conductor are likely to decrease, and as a result, problems such as plating defects may occur when Ni plating is performed on the thick-film conductor. Conversely, if the SiO2 content exceeds 60% by mass, the glass softening temperature becomes too high, and the adhesion between the thick-film conductor and the ceramic substrate may decrease.
[0032] Like the lead-free glass containing V and Zn described above, the lead-free glass not containing V may be crystallized glass or may not be crystallized glass. The shape of the glass powder not containing V is not particularly limited, and various shapes such as spherical and needle-like shapes can be used. However, unlike the lead-free glass powder containing V and Zn described above, the lead-free glass powder not containing V preferably has a D50 diameter (median diameter) of the volume cumulative particle size distribution measured by a particle size distribution meter using laser diffraction of 1 μm or more and 10 μm or less, and more preferably has a D50 diameter of 0.5 μm or more and 3 μm or less from the viewpoint of application when prepared in the form of a thick-film conductor paste and homogeneous dispersion with the conductive powder. If the D50 diameter exceeds 10 μm, it is likely to be difficult to homogeneously disperse the lead-free glass powder not containing V and the conductive powder with each other, and as a result, when prepared into a thick-film conductive paste, the glass powder not containing V is unevenly distributed in the paste, which may reduce the adhesive strength between the thick-film conductor and the substrate.
[0033] In addition to the lead-free glass powder containing V and Zn, the thick-film conductor forming composition according to the embodiment of the present invention may contain oxides as additives within a range that does not impair the effects of the present invention. Examples of such oxides include Bi2O3, SiO2, CuO, ZnO, TiO2, ZrO2, and Mn3O4, which have the function of improving the adhesive strength, acid resistance, solder wettability, etc. of the thick-film conductor, and one or more of these oxide powders may be added as necessary. However, from the viewpoint of suppressing the increase in resistance value due to temperature, it is preferable that the total content of these oxides is limited to about 10 parts by mass per 100 parts by mass of the conductive powder.
[0034] 2. Thick film conductor paste and preparation method thereof When preparing the thick-film conductor forming composition of the embodiment of the present invention described above, first, a conductive powder and a lead-free glass powder containing V and Zn are prepared as essential components, and glass powder or oxide not containing V is further prepared as necessary. Then, these are weighed out to a predetermined mixing ratio and mixed with a general powder mixer. In this way, a powdered thick-film conductor forming composition can be prepared. A solvent and a resin are added to this powdered thick-film conductor forming composition to a predetermined mixing ratio and kneaded to prepare a thick-film conductor paste. Terpineol, butyl carbitol, and the like used in general conductive pastes can be suitably used as the above solvent. In addition, ethyl cellulose, methacrylate, and the like used in general conductive pastes can be suitably used as the above resin.
[0035] The above resin and solvent may be mixed in advance to prepare an organic vehicle, and the organic vehicle may be kneaded with a powdered thick-film conductor-forming composition to prepare a thick-film conductor paste. From the viewpoint of cost and ease of handling, for example, a vehicle in which ethyl cellulose is dissolved in terpineol is preferably used as the organic vehicle. The blending ratio of the resin and the solvent constituting the organic vehicle is appropriately determined in consideration of the printability and application method of the thick-film conductor paste finally prepared, but generally, a blending ratio of about 100 to 2000 parts by mass of the solvent per 100 parts by mass of the resin is preferable.
[0036] When preparing a thick-film conductor paste using the above organic vehicle, the blending ratio of the organic vehicle is preferably 15 parts by mass or more and 250 parts by mass or less per 100 parts by mass of conductive powder, and more preferably 20 parts by mass or more and 100 parts by mass or less, taking into consideration printability, ease of application, suppression of particle settling in the thick-film conductor paste, and denseness of the thick-film conductor. If the blending ratio of this organic vehicle is less than 15 parts by mass, the viscosity of the thick-film conductor paste may become too high, making application substantially impossible, while conversely, if the blending ratio exceeds 250 parts by mass, problems such as particle settling in the thick-film conductor paste or a significant decrease in denseness of the thick-film conductor film after firing may occur.
[0037] There is no particular limitation on the method for kneading the powdered thick-film conductor forming composition with the organic vehicle, or the method for kneading the composition with a solvent and a resin when preparing the above-mentioned thick-film conductor paste. However, it is preferable to use a kneading machine such as a wet kneading mill, a roll mill, or a tapered roll mill, which allows efficient kneading.
[0038] 3. Thick film conductor and method for forming same The thick film conductor composition of the embodiment of the present invention is applied in the form of the above-mentioned thick film conductor paste onto a substrate having a glass-containing film formed on its surface, such as a glass glaze substrate, in a predetermined printing pattern, and then the thick film conductor is formed by subjecting the substrate to a firing process at a firing temperature depending on the application of the thick film conductor, preferably within a peak temperature range of 550 to 900°C.
[0039] The above-mentioned glass glaze substrate can be produced by applying a glass paste containing glass powder having a glass transition point of 400° C. or more to the surface of a ceramic substrate such as alumina and firing the glass paste, and the glass glaze layer formed by this is a film containing glass formed by the particles constituting the glass powder fusing or melting each other during the firing. This glass glaze layer generally contains various oxides in addition to SiO2 as the glass powder constituting the glass so as to have a glass transition point according to the application. The term "thick film conductor" is used for a thin film conductor formed by a thin film technique such as sputtering, and the film thickness is generally about 5 to 15 μm.
[0040] The thick-film conductor forming composition according to the embodiment of the present invention and the thick-film conductor paste prepared using the composition as a material have been described above with reference to the case where the thick-film conductor paste is applied to the surface of a glass glaze substrate and fired to form a thick-film conductor, but the present invention is not limited thereto, and can also be suitably applied to the case where the thick-film conductor paste is applied to the surface of an enamel substrate other than a glass glaze substrate and fired to form a thick-film conductor.Furthermore, the present invention can also be suitably applied to the case where the thick-film conductor paste is applied to the surface of a thick-film resistor and fired to form a thick-film conductor.
[0041] For example, as disclosed in Japanese Patent No. 2777206, when a thick-film resistor is produced by first applying, drying and firing a resistive paste containing RuO2 powder, glass powder and an organic vehicle to the surface of a ceramic substrate, and then applying, drying and firing a conductive paste containing a conductive powder such as Ag, glass powder and an organic vehicle to form an electrode, the thick-film conductor-forming composition according to the embodiment of the present invention can be suitably used as the material for this conductive paste. Next, the thick-film conductor-forming composition of the present invention will be described in more detail with reference to examples, but the present invention is not limited by these examples. EXAMPLES
[0042] A thick-film conductor paste prepared using each of the compositions was applied to a ceramic substrate having a glass glaze layer formed on its surface, and the thick-film conductor was formed by firing the paste. The surface condition of the thick-film conductor was evaluated. The following describes the preparation of the thick-film conductor powder, the preparation of the thick-film conductive paste, the preparation of the thick-film conductor, and the evaluation of the thick-film conductor.
[0043] [Preparation of thick-film conductor forming composition powder] First, three types of silver powders A, B, and C with different shapes and an alloy powder of silver and palladium were prepared as conductive powders constituting the composition for forming a thick-film conductor. Silver powder A is a spherical powder with a number average particle size of 0.3 μm, silver powder B is a scaly powder with a number average particle size of 15.0 μm, and silver powder C is a lump powder with a number average particle size of 1.0 μm. On the other hand, the alloy powder of silver and palladium is a spherical powder with a number average particle size of 0.2 μm. In addition, as the lead-free glass powder constituting the composition for forming a thick-film conductor, a lead-free glass powder containing V and Zn shown in Table 1 below and a lead-free glass powder not containing V shown in Table 2 below were prepared.
[0044] [Table 1]
[0045] [Table 2]
[0046] The glass transition points of the lead-free glass powder containing V and Zn shown in Table 1 were measured by TMA. The softening points of the lead-free glass powder not containing V shown in Table 2 were obtained by analyzing the glass powder by differential thermal analysis (TG-DTA) and were determined as the peak temperature at which the next differential thermal curve on the higher side decreased from the temperature at which the lowest side of the differential thermal curve decreased. Furthermore, powdered Bi2O3 and V2O5 were prepared as additives. These conductive powders, lead-free glass powders, and additives were weighed out and mixed in a powder mixer to obtain the blending ratios shown in Table 3 below, to prepare compositions for forming thick-film conductors in Examples 1 to 9 and Comparative Examples 1 to 5. The total glass mass parts are the total amount of the lead-free glass powder containing V and Zn and the lead-free glass powder not containing V relative to 100 parts by mass of the conductive powder, and the V glass mass parts are the amount of the lead-free glass powder containing V and Zn relative to 100 parts by mass of the conductive powder.
[0047] [Table 3]
[0048] [Preparation of thick-film conductive paste] Next, ethyl cellulose was weighed out and mixed to give a blending ratio of 7 mass% and terpineol solution as a solvent of 93 mass%, and then the ethyl cellulose was dissolved by heating to prepare an organic vehicle. The obtained organic vehicle was weighed out and charged into a three-roll mill for each of the thick-film conductor forming composition powders of Examples 1 to 9 and Comparative Examples 1 to 5 prepared above to give the blending ratios shown in Table 3 above, and then kneaded to prepare a thick-film conductor paste.
[0049] [Preparation of thick-film conductors] Fourteen types of thick-film conductor pastes containing the thick-film conductor forming compositions of Examples 1 to 9 and Comparative Examples 1 to 5 thus prepared were screen-printed on the surface of a glass glaze substrate by a screen printer (coating process), dried at 150°C for 5 minutes using a belt-type drying furnace (drying process), and fired at a peak temperature of 600°C for 5 minutes using a belt furnace (firing process). In addition, in the screen printing of the thick-film conductor paste, the printing conditions were adjusted so that the film thickness after firing would be 10 μm. In this way, 14 types of thick-film conductors were manufactured.
[0050] The above glass glaze substrate was a 96% alumina substrate (25.4 mm long x 25.4 mm wide x 1 mm thick) with a 20 μm thick glass glaze layer formed by firing on the entire surface. The glass glaze layer was formed by applying a glass glaze paste prepared by kneading 80% by mass of lead-free glass powder (containing 1% by mass of B oxide B2O3, 22% by mass of SiO2, 3% by mass of Al2O3, 1% by mass of ZnO, and 73% by mass of Bi2O3) with a softening point of 600°C measured by TG-DTA and 20% by mass of the same organic vehicle as used in the above thick-film conductor paste using a three-roll mill, drying the paste at 150°C for 5 minutes using a belt-type drying furnace, and firing the resulting dried film in a belt furnace with a peak temperature of 600°C for 5 minutes.
[0051] [Thick film conductor evaluation] First, in order to evaluate the surface condition of each of the 14 types of thick-film conductors prepared above, images were taken with an SEM to check for the presence or absence of protruding glass components. As a result, protruding substances thought to be glass components were confirmed on the surface of the thick-film conductor in all comparative examples except for comparative example 5. FIG. 1 shows an SEM photograph of the thick-film conductor of comparative example 1. In FIG. 1, it can be seen that the particle group constituting the conductive powder is sintered under the film made of the protruding glass components. On the other hand, in all of the thick-film conductors in Examples 1 to 9, protruding substances thought to be glass components, as in Comparative Examples 1 to 4, were not confirmed on the surface of the thick-film conductor. FIG. 2 shows an SEM photograph of the thick-film conductor of Example 1.
[0052] In addition, images were taken with an SEM to check whether stains were present around the thick-film conductor on the surface of the glass glaze layer. As a result, stains were observed on the surface of the glass glaze layer around the thick-film conductor in Comparative Examples 4 and 5, but not elsewhere.
Claims
1. The present invention includes a conductive powder and a lead-free glass powder containing vanadium and zinc, and is used as a raw material for a thick-film conductor layer formed by firing on a substrate having a glass-containing film formed on the surface thereof, The composition for forming a thick-film conductor is characterized in that the conductive powder is a single metal powder or an alloy powder selected from the group consisting of Au, Ag, Pd, and Pt, and the lead-free glass powder is a V 2 O 5 -ZnO-Bi 2 O 3 based glass powder, containing 30 to 60 mass % of the vanadium calculated as V 2 O 5 oxide and 20 to 50 mass % of the zinc calculated as ZnO oxide.
2. 2. The composition for forming a thick-film conductor according to claim 1, wherein the lead-free glass powder has a glass transition point of 350° C. or more and 550° C. or less.
3. 3. The composition for forming a thick-film conductor according to claim 1, further comprising a glass powder not containing vanadium.
4. A thick-film conductor paste comprising the composition for forming a thick-film conductor according to claim 1 and a vehicle.
5. A thick-film conductor formed on the surface of a glass-containing film formed on a substrate, the thick-film conductor comprising a conductive material and glass, the conductive material being an element or alloy of an element selected from the group consisting of Au, Ag, Pd, and Pt, the glass being a V 2 O 5 -ZnO-Bi 2 O 3 -based glass containing 30 to 60 mass % vanadium calculated as V 2 O 5 oxide and 20 to 50 mass % zinc calculated as ZnO oxide.
Citation Information
Patent Citations
Composition for conductive film formation
JP1990234308A
Thermal printing head, heating resistor used in the same, and method of manufacturing the heating resistor
JP2002127483A
Thermal head
JP2010158873A
Conductive composition, and method for manufacturing terminal electrode
JP2017199544A
Conductive composition, method for manufacturing conductor, and method for forming wiring of electronic component
JP2018190491A